Analyzing Pro-Environmental Planned Behavior in SMEs: Unveiling Green Innovation Intentions - Durman, Theodosia Yunita; Nadlifatin, Reny (Relevance: Journal of Management and Business, 2024)
The challenge of drastic global climate change has urged a transition to a green economy. The contribution of SMEs as an engine of macroeconomic expansion that pays attention to and makes environmental issues a basic concept of their business model is very important. This study aims to investigate the factors that influence the behavioral intention of SMEs in tourism areas in Labuan Bajo to conduct green innovation using an integrated approach of Pro environmental planned behavior (PEPB). Offline questionnaires and interviews were used as data collection tools, and 205 SMEs that have conducted green innovation were respondents. The theoretical model was tested using partial least squares structural equation modeling (PLS-SEM) with top-level constructs. The findings of this study reveal that perceived authority support, perceived environmental concern, subjective norm, attitude, significantly affect the intention of SMEs to do green innovation. Meanwhile, perceived behavioral control are known to be insignificant. These findings contribute to the development and validation of an integrated model of green innovation in SMEs and provide all business stakeholders with an understanding of the rationale for green innovation.